Kualitas Tidur Berhubungan dengan Perubahan Tekanan Darah pada Lansia - Harsismanto J; Juli Andri; Tirta Dwi Payana; Muhammad Bagus Andrianto; Andry Sartika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the relationship of sleep quality with changes in blood pressure in elderly hypertension at Tresna Werdha Social Home (PSTW) Bengkulu Province. This type of research is quantitative research in the form of an analytic survey with a cross-sectional research design. Univariate analysis results showed blood pressure in hypertensive elderly at Tresna Werdha Social Home (PSTW), which is 12 respondents (54.5%) had mild hypertension, ten respondents (45.5%) had moderate hypertension. Sleep quality experienced by elderly hypertension, 11 respondents (50%) experienced good sleep quality, and 11 other respondents (50%) experienced poor sleep quality. The results of bivariate analysis using chi-square test obtained ρ value = 0,000 and C value = 0.674. In conclusion, there is a significant relationship between sleep quality and changes in blood pressure in hypertensive elderly at Tresna Werdha Social Home (PSTW) in 2019. Poor sleep quality affects changes in elderly blood pressure. Keywords: Sleep Quality, Elderly, Blood Pressure